A PHILOSOPHY IN ACCOUNTING: Perception, Accruals, Fraud – A Literature Review with Future Research Direction - ADININGSIH, TRIANA EVA (Berkala Akuntansi dan Keuangan Indonesia, 2024)
This study uses bibliometric techniques to review the perception, accruals, and fraud literature systematically. The study examines the intellectual structure of this literature by conducting bibliographic coupling analyses. Additionally, the study maps the major conceptual themes in this literature using co-word analysis. Based on the findings, the study proposes a research agenda highlighting opportunities for theoretical development in the perception, accruals, and fraud literature. The study's findings can lead to future research directions and offer insights into the state of the field's investigation at the present time.